Retargeting - the case of landing jobs - Pereira, Miguel Santos (2020)
In this dissertation it was intended to study how an online advertising technique called retargeting can help Landing.jobs on its marketing efforts. In order to do that, a research methodology mixing both quantitative and qualitative research methods was created, considering the company’s expectations for this study as well as the research objective that was defined. Through the analysis of three different advertisements, it was concluded that this technique may yield more effective results than other similar techniques. As such, the findings of this study may help not only to steer future lines of research on related subjects in the best direction, but also other businesses apply the same strategy, in order to create more effective advertisements targeting niche audiences.